2010
DOI: 10.1051/0004-6361/201014788
|View full text |Cite
|
Sign up to set email alerts
|

The optical counterpart to IGR J06074+2205: a Be/X-ray binary showing disc loss andV/Rvariability

Abstract: Context. Current X-ray missions are regularly discovering new X/γ-ray sources, so identifying the counterparts of these high-energy sources at other wavelengths is important for determining their nature. In particular, optical observations are crucial in the study of X-ray binary populations in our Galaxy. Aims. The main goal of this work is to determine the properties of the optical counterpart to the INTEGRAL source IGR J06074+2205 and study its long-term optical variability. Although its nature as a high-ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…A number of studies were dedicated to the search of the optical counterpart of this source (Halpern and Tyagi, 2005;Tomsick et al, 2006b;Masetti et al, 2006a;Reig and Zezas, 2009;Reig et al, 2010). Finally Reig et al (2010) identified it with a relatively bright (V = 12.3) B0.5Ve star located at a distance of ∼ 4.5 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were dedicated to the search of the optical counterpart of this source (Halpern and Tyagi, 2005;Tomsick et al, 2006b;Masetti et al, 2006a;Reig and Zezas, 2009;Reig et al, 2010). Finally Reig et al (2010) identified it with a relatively bright (V = 12.3) B0.5Ve star located at a distance of ∼ 4.5 kpc.…”
Section: Discussionmentioning
confidence: 99%
“…From the occurrence of the two similar single-peaked profile states (in May 2016 and July 2017), we can infer a tentative period of the rotation of the density wave around the star of P dens-wave ∼ 420 d. This period is rather short when compared with periods observed in isolated Be stars, which typically range between five to ten years (Okazaki 1997). However, it has been shown that the V/R quasi periods of Be star discs in Be/XB systems are significantly shorter (Clark et al 1998;Reig et al 2010) owing to the smaller size of the discs in these systems (Reig et al 2016).…”
Section: V/r Variability and Discovery Of A Retrograde One-armed Densmentioning
confidence: 99%
“…In common with other BeXBs (Reig et al 2005(Reig et al , 2010b, asymmetric profiles are not seen until the disc reaches certain size and density. During the initial stages of disc growth, the shape of the Hα line is always symmetric.…”
Section: Referencesmentioning
confidence: 63%